IoT-based Child-in-Car Safety Reminder - Taufiq Dzulkifli, Muhammad; Yahya, Roshayati (Evolution in Electrical and Electronic Engineering, 2021)
There are many cases related to the child being trapped inside a locked car with a window and engine closed, such as children being trapped inside the car due to the parents rushing to their workplace. In order to save the children from being trapped inside a car, a safety reminder is created by connecting the PIR motion sensor and microcontroller with the mobile phone through an application. This system used the Internet of Things (IoT) which occurs during connecting the system with the phone. Besides, the motion sensor that is included inside the system has the ability to detect human movement inside the car. This system is believed to be useful towards the safety of children efficiently so that the children will live a happy life. When the system detected the movement of a trapped child inside the car, the system will send a notification to the parents through mobile application.